Magnus effect and dynamics of a spinning disc in a rarefied medium - Mishuris, G.
MAGNUS EFFECT consists in deflection of the trajectory of a rotating body moving in a gas. It is a direct consequence of the interaction between the body surface and the gas particles. In this paper, we study the so-called inverse Magnus effect which can be observed in rarefied gases. We restrict ourselves to the two-dimensional case, namely a spinning disc moving through a sparse zero-temperature medium. We consider general non-elastic interaction between the disc and the particles depending on the incidence angle. We give a classification of auxiliary parameters with respect to possible dynamical response. In the absence of other forces, three kinds of trajectories are possible: (i) a converging spiral, (ii) a curve converging to a straight line and (iii) a circumference, the case intermediate between the two first ones. A specific 2-D parameter space has been introduced to provide respective classification. © 2009 by IPPT PAN.